Power games: Using Foucault to shed light on the inherent power dynamics of intercultural Bible study groups. Discussion of a qualitative research project - van der Walt, Charlene (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
In theory the process of intercultural Bible reading should create a safe space where the voice of the individual can be heard in community with others. It should be a space where the individual is not only free to speak, but also to have the innate experience of truly being heard. In this respect the intercultural Bible reading experience becomes a space that promotes human dignity and has the inherent capacity to facilitate social transformation. Although these Bible study groups can ideally be a safe space with the potential for social transformation, the practical reality shows a more complicated dynamic. An important factor that contributes to the complexity is the underlying power dynamic in the social interaction. To bring the concept of power in intercultural Bible reading into focus, an empirical study was conducted. After briefly discussing the scope of the empirical research project, the main focus of the paper will shift to Michel Foucault’s seminal theory on power. Conversation analysis was used in the research project as a qualitative data analysis tool to identify the main trends functioning in the observable power dynamic. Foucault’s theory will be used to shed light on the inherent power dynamic that functions in the intercultural Bible reading space. The paper will show that the intercultural Bible reading space cannot escape the functioning of an inherent power dynamic, but by using Foucault’s theory, a greater understanding can be obtained and observed trends and patterns can be better understood, predicted and managed.